The Influence of Return On Assets (ROA), Return On Equity (ROE), Return On Investment (ROI), and Earning Per Share (EPS) on Company Value in the Automotive industry and its components listed on the BE - Nurapiah; Rukhayati; Qosim, Nanang; Latoki, Labandingi (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
This research aims to analyze the influence of Return On Assets (ROA), Return On Equity (ROE), Return On Investment (ROI), and Earning Per Share (EPS) on the value of companies in the automotive industry and its components listed on the Indonesia Stock Exchange (BEI). The ever-fluctuating development of the automotive world requires companies that are members of this industry to be able to maintain their existence in the face of changing situations, both domestic and international. Apart from that, companies also have to compete with similar competitors, both from within and outside the country. The comp. This research uses a purposive sampling method to obtain a representative sample according to the specified criteria. The analytical tool used is panel regression analysis any's capabilities can be seen through the information contained in the annual financial report. The research results show that Return On Assets (ROA) and Return On Investment (ROI) have a positive, although not significant, effect on company value on the BEI. Meanwhile, Return On Equity (ROE) and Earning Per Share (EPS) have a negative and insignificant effect on company value on the BEI (study of the automotive industry and its components).